Investigating the Impact of Transport Services and Renewable Energy on Macro-Economic and Environmental Indicators - Liu, Jinghua; Quddoos, Muhammad Umer; Akhtar, Muhammad Hanif; Amin, Muhammad Sajid; Yu, Zhang; Janjua, Laeeq Razzak (Frontiers in Environmental Science, 2022)
A global shift toward renewable energy has proved to be a major constituent in drifting toward climate change. Given the context, the present research study focuses on the nexus between renewable energy, transport services, and performance on economic and environmental fronts. The study has employed an ARDL time series approach to test the effects of hypothesized relationships for the period from 1989 to 2020. The results of the study divulge that the consumption of RE is inversely and significantly coupled with the economic and environmental performance indicators, validating the notion that Romania has emerged as a leading renewable energy user. Foreign direct investment inflows in Romania are significantly and positively associated with the economic and environmental performance indicators. However, the impact of foreign direct investment inflows tends to be smaller than that of the forest area and renewable energy. All the exogenous variables appear to affect the economic and environmental performance indicators significantly in the short run. Furthermore, the forest area is negatively linked with the economic and environmental performance indicators in the Romanian economy. Based on the outcomes of the research, policy prescriptions are suggested to safeguard against environmental degradation and support growth in the much-needed forest resources.